2017
DOI: 10.1007/s00296-017-3910-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after rheumatoid arthritis patients complete their participation in a long-term observational study with tofacitinib combined with methotrexate: practical and ethical implications in vulnerable populations after tofacitinib discontinuation

Abstract: To describe disease activity and disability during the first year of follow-up, from rheumatoid arthritis (RA) patients who discontinue tofacitinib after they end participation in a clinical trial. From 2008 to 2016, 36 patients were enrolled in the "Long term follow-up study with tofacitinib (and methotrexate) for RA treatment". At the end of the study, tofacitinib was discontinued and patients were proposed to enter an observational study; 35 agree and had scheduled evaluations at baseline, at 15 and 30 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Recently, two studies examined the outcomes of tofacitinib discontinuation during 1 year of post-treatment follow-up among RA patients who had achieved remission or low CDAI in clinical trials and long-term extension studies [21,22]. Among these studies, one conducted in a Japanese cohort showed that 37% (20 out of 54 patients) in the discontinuation group continued without flare while tofacitinib-free [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two studies examined the outcomes of tofacitinib discontinuation during 1 year of post-treatment follow-up among RA patients who had achieved remission or low CDAI in clinical trials and long-term extension studies [21,22]. Among these studies, one conducted in a Japanese cohort showed that 37% (20 out of 54 patients) in the discontinuation group continued without flare while tofacitinib-free [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, one conducted in a Japanese cohort showed that 37% (20 out of 54 patients) in the discontinuation group continued without flare while tofacitinib-free [21]. In another study in Mexican patients, disease activity worsened following discontinuation of tofacitinib in 85% (17 out of 20 patients) [22]. In the present study in Japanese patients, the probability of flare-free survival at 12 months as estimated by the Kaplan-Meier approach was 32% in the discontinuation group, 66% in the dose-reduction group, and 94% in the continuation group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Особый интерес представляют исследования, касающиеся оптимизации терапии РА после достижения ремиссии, а именно -снижения дозы препаратов или отмены терапии [124,125]. В одном наблюдательном исследо-вании было показано, что у 37% (20 из 54) пациентов после отмены ТОФА не наблюдалось обострения заболевания [126], а по данным другого исследования, обострение заболевания после отмены ТОФА имело место у 85% (17 из 20) пациентов [127]. Представляют интерес материалы проспективного исследования, в которое вошли 100 пациентов с высокой/умеренной активностью РА, получавшие лечение ТОФА (5 мг 2 раза в день) [128].…”
Section: таблицаunclassified
“…Особый интерес представляют исследования, касающиеся оптимизации терапии РА после достижения ремиссии, а именно изучение возможности снижения дозы препаратов или отмены терапии [74]. В двух исследованиях отмена ТОФА приводила к развитию обострения у 63% [75] и 85% пациентов [76]. В проспективном исследовании [77] вероятность сохранения ремиссии после прекращения лечения ТОФА составила 32%, а повторное назначение препарата позволило быстро достичь ремиссии у 93% пациентов, у которых ТОФА был отменен, и у 100% пациентов, у которых развитие обострения имело место при снижении дозы ТОФА.…”
Section: эффективностьunclassified